Layered Contracts : Both Legally Functional and Human-Friendly - Waller, Robert; Passera, Stefania; Haapio, Helena (Springer, 2022)
This paper addresses a debate that frequently arises when contract simplification is discussed. For business users, a clear contract is one that helps them understand the deal, implement its terms and encourages a productive business relationship. Legal teams, on the other hand, often worry about their responsibility to protect their client against excessive risk and potential litigation. For them, a clear document is unambiguous and legally watertight, resulting in complex documents that can be hard for non-lawyers to use. In this paper we discuss a layered approach that can reconcile competing definitions of clarity, functionality and user needs, and we speculate about the role of information design and emerging technologies in the development of human-centred layers to traditional contract wording.
Keywords: fi=Talousoikeus|en=Business Law|